Analysis of bio-oil from palm oil wastes through batch pyrolysis process - Saifuddin, Seth (2009)
Malaysia is well known as the top largest producer of palm oil in the world. The abundance of biomass from palm oils agriculture industry would make a great benefit is they were used as a new source in fulfilling energy demand which increased year by years. The biomass can be converted into valuable product via pyrolysis process. Pyrolysis is thermal degradation either in the complete absence of oxidizing agent which is air or oxygen. The products of pyrolysis are bio-oil, char and gas. In this research, the pyrolysis of palm oil wastes (Pump Kernel Shell (PKS), Empty Fruit Bunch (EFB) and Mesocarp Fiber) was performed using a static batch reactor which being heated by a tubular furnace. Preliminary analysis was conducted using thermogravimetric analyzer (TGA) to determine the volatility, ash residue, moisture content and weight loss. 3 different physical properties were investigated on these bio-oils which are water content, pH, and viscosity. The functional groups of the product which is bio oil are identified by using Fourier Transform Infrared spectrometer (FTIR). Gas Chromatography-Mass Selectivity (GC-MS) was used to identify the component exists in the bio-oils. From the result, the pHs for all products were very acidic with pH value are 2.46, 2.53 and 2.56 respectively for Pump Kernel Shell (PKS), Empty Fruit Bunch (EFB) and Mesocarp Fiber. The viscosity values range was 33-43 cP and the water content in the bio-oils were 7-13 % weight. The result of FTIR and GC-Ms shows that, there are many complex compounds which would be a ideal for chemical feedstock and with undergoing upgrading process, can be used as fuel.